Adolescent Eating Behavior: The Role of Indulgent Parenting. Issue 4 (October 2015) - Darling, Carol A.; Rehm, Marsha; Coccia, Catherine; Cui, Ming
This qualitative study was set in the context of two evolving concomitant social issues: concerns with adolescent eating and health behaviors and parental indulgence. The research purpose was to gain a deeper and more insightful understanding of the family food ecosystem, parental modeling, and parental indulgence and their potential relationship to adolescent health and well-being. In all, 29 parents of 25 high school students were interviewed, and the resulting narrative data were analyzed for themes. Results showed parental concerns about weight and health, modeling of unhealthy eating habits, and soft structure as a prevalent form of parental indulgence. This research has implications for social workers, family service providers, and health providers who work with communities in developing nutrition and health education programs and policies that enhance parental knowledge, limit the effects of parental indulgence, and address adolescent decision-making skills related to their own health. Recommendations are provided to improve services for families.